2015
DOI: 10.1177/0309364614528204
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study on the efficacy of SpinoMed® and soft lumbar orthosis for osteoporotic vertebral fracture

Abstract: In this study, SpinoMed® could not provide additional treatment benefits to patients with osteoporotic vertebral fracture regarding pain relief and functional independence improvement at the subacute stage. The effects of SpinoMed® in muscle-strengthening and thoracic kyphotic angle reduction for patients with osteoporotic vertebral fracture need to be further verified in a more intensive and longer-term training program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 24 publications
(24 reference statements)
4
52
1
Order By: Relevance
“…Eventually, 10 articles were included in this study (10111213141516171819) and 4 RCTs, with 281 participants, were included in meta-analysis (10111214) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, 10 articles were included in this study (10111213141516171819) and 4 RCTs, with 281 participants, were included in meta-analysis (10111214) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…As summarized in Table 1 and 2, 6 RCTs (101112131415), 1 non-randomized controlled trial (19) and 3 observational studies (161718) were included. Characteristics of studies varied a lot but all had limited number of participants and only one trial had a sample size merely above 100 (12).…”
Section: Resultsmentioning
confidence: 99%
“…Being a female, age 76, with back pain secondary to osteoporotic vertebral fractures of the T11 and T12 vertebrae, our patient met all of the study inclusion criteria of: "female, age 55 or above, clinical diagnosis of OVF with radiographs, back pain secondary to OVF, and affected vertebra between T1 and L5". 5 When comparing SpinoMed® and soft lumbar orthosis, statistically significant improvements were observed for all three groups (hard brace, soft brace, and no brace) between pretreatment and post-treatment for pain. However, investigators were unable to prove a statistically significant difference between the groups.…”
Section: Critical Appraisalmentioning
confidence: 91%
“…The characteristics of these three studies were reviewed, and one study was chosen as most relevant and valid to the clinical question. 5 This study was re-located in Google Scholar, and the related articles function was used. This revealed a relevant trial with only 13 cases, which was considered too small to add value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors also concluded that the effects of this medical device in muscle-strenghtening and thoracic kyphotic angle reduction for patients with osteoporotic vertebral fracture need to be further verified in a more intensive and longerterm training program (9).…”
Section: Spinal Orthosesmentioning
confidence: 99%